DEVELOPING MOOC-BASED VIDEO CONTENT FOR CREATING SUPPORTIVE LEARNING ENVIRONMENTS IN SPEAKING COURSES FOR EFL LEARNERS - Elvira Rosyida M.R.; Ira Maria Fran Lumbanbatu (Indonesian EFL Journal, 2024)
MOOC (Massive Open Online Courses) represents a pivotal point in language learning, as this platform can facilitate various forms of learning materials such as handouts, instructional videos, and online assignments. In this study, the authors focus on developing MOOC for the course Speaking for Academic Purposes, providing engaging and easily understandable materials for its users. The research was conducted by applying the research and development design known as the R & D cycle. It was adapted and simplified into five stages: research and information collection, product development, expert validation, field testing, and final product. Having conducted the research, the writers consider that the developed MOOC-based video content product is feasible for English Department students. Based on the expert validation, the product obtained a 95.8% feasibility score, while in the field research, the product achieved an 89.9% feasibility score. The final product serves as valuable speaking materials for both teachers and students, underscoring the study's significance in enhancing language education through innovative online learning tools.